(untitled) (Collection of scientific works «Modern structures of metal and wood», 2024)
The article describes in detail the complete engineering methodology for the verification calculation of steel grain storage structures based on the pan-European Eurocode standardisation system in accordance with the provisions of DBN B.2.6-221:2021 and DSTU-N B EN 1991-4. The emphasis of the work is on determining the mechanisms for regulating the reliability of grain storage structures within the framework of the application of semi-probabilistic calculation in the form of the limit state method. To assess the stress-strain state of individual structural elements of the silo, two methods were used: the direct method of finite element analysis without taking into account the effects of geometric and physical nonlinearity and the theoretical method based on the membrane theory in a linear-elastic formulation assuming linear-elastic material characteristics and the linear theory of small deformations. The practical implementation of the methodology was tested on the example of real steel silo structures. It is established that the change in the level of reliability of steel grain storage structures within the framework of the limit state method is carried out through a system of partial coefficients that take into account the stochastic properties of external influences, variability of material characteristics, types of calculations, the degree of importance of structural elements in the structure and the degree of responsibility of the silo as part of the enterprise. The specified values of the partial reliability factors are governed exclusively by the regulatory requirements and guidelines of the national annex and cannot be adjusted by the design specification. The given values of the coefficients are limited to limit state checks on the bearing capacity and serviceability of structures under static load, including cases where the dynamic impact is assessed using equivalent quasi-static loads with appropriate amplification factors.